Investigation on Temperature-Dependent Multiaxial Ratchetting of Polycarbonate by a Novel Experimental Method - Fucong Lu; Kun Zhang; Yuhang Hou; Zhiwen Wu (Advances in Materials Science and Engineering)
A novel method to heat the multiaxial hollow thin-wall specimen was proposed, where its gauge length section can be heated by the liquid (i.e., water) filled inside the specimen instead of the closed furnace. This method realizes the direct measurement of multiaxial strain on the surface of specimen at different temperatures by the noncontact digital image correlation. By utilizing the proposed method, the multiaxial stress-control cyclic tests were performed to investigate the multiaxial ratchetting of polycarbonate (PC) at different temperatures. It is found that the multiaxial ratchetting of PC depends greatly on the test temperatures and the multiaxial ratchetting strain increases with increasing the test temperature. The temperature-dependent multiaxial ratchetting is also influenced by valley stresses. The unrecoverable part of deformation in the multiaxial ratchetting strain increases with increasing temperature.